Perspectives on Urban Climate Change and Policy Measures in India - Salahuddin Qureshi (National Geographical Journal of India, 2022)
This paper is an attempt to outline the distinct features of urban micro climate from the climate of the countryside which we are generally familiar of. The study has also tried to distinguish the concept of urban climate change from that of global warming. The paper identifies the major causes of urban climate change as well as the remedial policy measures for a better climate change adaptation. The climates of large cities, particularly the megacities, considerably vary from the climate of villages in the outer fringe. Megacities experience 40 to 80C higher temperatures than the climate of the city region. The study finds that the urban climate is experiencing increasing weather extremity and uncertainty in proportion to urban hierarchy. The study reveals a further challenging nocturnal climatic condition in the major cities because of increasing thermal inversion. Growing urban heat island intensity in the already hotter tropical cities is more challenging than the temperate cities of higher climate change resilience. The urban climate is becoming considerably challenging in the Indian cities because our megacities are highly congested and crowded than the major cities of Brazil, China and Indonesia. Urban climate change threatens a poor quality of life to the middle class and the migrant labour in the developing countries like India, where despite a lower percentage of urbanization, there is much higher concentration and crowding in the few big cities